2006
DOI: 10.1159/000094271
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Occult Hepatitis B Virus Infection among Omani Blood Donors: A Preliminary Study

Abstract: Objectives: The aim of this study was to determine the prevalence of hepatitis B surface antigen (HBsAg), hepatitis B core antibodies (anti-HBc) and hepatitis B virus (HBV) DNA among a selected group of Omani blood donors. Materials and Methods: Two hundred HBsAg-negative donors were screened for anti-HBc. Those found to be positive were investigated for HBV DNA by polymerase chain reaction. HBsAg was retested on these sera following an immune complex dissociation technique. Results: HBsAg was present in 2.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
(27 reference statements)
3
15
0
2
Order By: Relevance
“…Meanwhile, the logistic regression analysis showed that history of blood transfusion was one of the independent risk factors for HBV infection. This latter finding matches well with other published data [11]. It has been reported that despite continued improvements in the selection criteria of blood bank donors and of the applied serological tests protocol in sample evaluation, the transmission of HBV infection by blood transfusion still occurs in a proportion of cases even if the transfused blood tested negative for HBsAg using highly sensitive assays [12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, the logistic regression analysis showed that history of blood transfusion was one of the independent risk factors for HBV infection. This latter finding matches well with other published data [11]. It has been reported that despite continued improvements in the selection criteria of blood bank donors and of the applied serological tests protocol in sample evaluation, the transmission of HBV infection by blood transfusion still occurs in a proportion of cases even if the transfused blood tested negative for HBsAg using highly sensitive assays [12].…”
Section: Discussionsupporting
confidence: 91%
“…It is a marker of acute, chronic or resolved infection and remains detectable for life [14]. The reported prevalence of anti-HBc markers among donors at blood banks varies in other published studies depending on the local prevalence of HBV, ranging from 0.4% in low-endemic areas to 70% in high-endemic areas [11,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of asymptomatic adult blood donors in Oman found that 20% had evidence of earlier infection by hepatitis B with only 2.5% showing HbsAg positivity at the time of testing. 18 Our study was small and not community-based, therefore little inference can be drawn regarding the prevalence of hepatitis B in Omani children.…”
Section: Discussionmentioning
confidence: 88%
“…Bu nedenle HBsAg testlerinin duyarlılığını artırmak amacıyla Chemiluminescence Immunassay (CLIA), HBsAg yoğunlaştırma ve immünkompleks ayrıştırması gibi yöntemler ile ilgili çalışmalar yapılmakta veya uygulanmaktadır [61][62][63]. OHB'nin özellikle transfüzyon ile HBV bulaşına neden olabileceği bilinmektedir ve HBsAg testlerinde yenilikler olsa da HBV belirteci olarak tarama testlerinde HBsAg'nin kullanımında bazı problemler oluşabilir.…”
Section: Tanı Ve Taramaunclassified